Premature pulmonary valve opening in a patient with absent tricuspid valve. Issue 6 (December 1980) - D'Cruz, I A; Shah, S N; Levinsky, R; Goldbarg, A
Abstract : Echocardiography (M-mode and cross-sectional) disclosed premature opening of the pulmonary valve (very deep "a" wave) in a young man who underwent tricuspid valvulectomy without valve replacement 32 months before for refractory bacterial endocarditis. Cardiac catheterisation showed a prominent atrial wave on the pulmonary artery pressure curve. Thus, part of the right ventricular ejection appeared to occur before the onset of ventricular systole, as a result of powerful right atrial contraction.